2021
DOI: 10.1302/2633-1462.212.bjo-2021-0108.r1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment is not cost-effective compared to nonoperative treatment for displaced distal radius fractures in patients 65 years and over

Abstract: Aims The purpose was to compare operative treatment with a volar plate and nonoperative treatment of displaced distal radius fractures in patients aged 65 years and over in a cost-effectiveness analysis. Methods A cost-utility analysis was performed alongside a randomized controlled trial. A total of 50 patients were randomized to each group. We prospectively collected data on resource use during the first year post-fracture, and estimated costs of initial treatment, further operations, physiotherapy, home nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Other studies have reached varying conclusions on the relative cost effectiveness of treatment options for DRFs. In a randomized study of patients aged 65 years and older with displaced DRFs, Hassellund et al 24 found that volar plating was not cost effective compared with nonsurgical treatment from the health care perspective despite significantly higher health-related quality of life associated with surgical treatment. In a randomized study of patients aged 50–74 years with unstable dorsally displaced fractures, Saving et al 25 found that volar plating resulted in higher costs and a smaller quality of life benefit compared with external fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reached varying conclusions on the relative cost effectiveness of treatment options for DRFs. In a randomized study of patients aged 65 years and older with displaced DRFs, Hassellund et al 24 found that volar plating was not cost effective compared with nonsurgical treatment from the health care perspective despite significantly higher health-related quality of life associated with surgical treatment. In a randomized study of patients aged 50–74 years with unstable dorsally displaced fractures, Saving et al 25 found that volar plating resulted in higher costs and a smaller quality of life benefit compared with external fixation.…”
Section: Discussionmentioning
confidence: 99%
“…All transition-state probabilities and ranges can be seen in Table 1 . 3 , 5 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , …”
Section: Methodsunclassified
“…With a willingness to pay €27 500 per QALY, there was a 45% chance of the operative treatment being effective. The authors concluded that operative treatment was not cost-effective from a healthcare perspective, Hassellund et al [ 27 ]. The cost effectiveness of different operative treatment options in the older population have also been studied.…”
Section: Discussionmentioning
confidence: 99%
“…I 2021 ble det fremmet et ønske om at prioriteringsforskriften også skulle omfatte primaerhelsetjenesten (Meld. St. 38 (2020-2021), men det er fortsatt ikke utarbeidet en forskrift.…”
Section: øKonomisk Evaluering Av Helsetiltak Funclassified